Enhancing the doubly-longitudinal polarization in WZ production at the LHC - Dao, Thi Nhung; Le, Duc Ninh (Communications in Physics, 2023)
We present new results for the theoretical prediction of doubly-polarized cross sections of \(WZ\) events at the LHC using leptonic decays. Compared to the previous studies, two new kinematic cuts are considered. These cuts are designed to enhance the doubly-longitudinal (LL) polarization and, at the same time, study the Radiation Amplitude Zero effect. We found a new cut on the rapidity separation between the \(Z\) boson and the electron from the \(W\) decay which makes the LL fraction largest, namely \(|Δ y_{Z,e}| < 0.5\). This result is obtained at the next-to-leading order in the strong and electroweak couplings.